Transforming growth factor-β1 decreases erythropoietin production through repressing hypoxia-inducible factor 2α in erythropoietin-producing cells - Hong-Mou Shih (BMC, 2021)
Abstract Background Renal erythropoietin (EPO)-producing (REP) cells produce EPO through hypoxia-inducible factor (HIF) 2α-activated gene transcription. Insufficient EPO production leads to anemia in patients with chronic kidney disease. Although recombinant EPO is effective to improve anemia, no reliable REP cell lines limit further progress of research and development of novel treatment. Methods We screened Epo mRNA expression in mouse fibroblast cell lines. Small interfering RNA specific for HIF1α or HIF2α was transfected to study Epo expression in C3H10T1/2 cells. The effect of transforming growth factor-β1 (TGF-β1) on HIF-EPO axis was studied in C3H10T1/2 cells and mice. Results Similar to mouse REP pericytes, C3H10T1/2 cells differentiated to α-smooth muscle actin+ myofibroblasts after exposure to TGF-β1. Specific HIF knockdown demonstrated the role of HIF2α in hypoxia-induced Epo expression. Sustained TGF-β1 exposure increased neither DNA methyltransferase nor methylation of Epas1 and Epo genes. However, TGF-β1 repressed HIF2α-encoding Epas1 promptly through activating activin receptor-like kinase-5 (ALK5), thereby decreasing Epo induction by hypoxia and prolyl hydroxylase domain inhibitor roxadustat. In mice with pro-fibrotic injury induced by ureteral obstruction, upregulation of Tgfb1 was accompanied with downregulation of Epas1 and Epo in injured kidneys and myofibroblasts, which were reversed by ALK5 inhibitor SB431542. Conclusion C3H10T1/2 cells possessed the property of HIF2α-dependent Epo expression in REP pericytes. TGF-β1 induced not only the transition to myofibroblasts but also a repressive effect on Epas1-Epo axis in C3H10T1/2 cells. The repressive effect of TGF-β1 on Epas1-Epo axis was confirmed in REP pericytes in vivo. Inhibition of TGF-β1-ALK5 signaling might provide a novel treatment to rescue EPO expression in REP pericytes of injured kidney.